New species of Mongrel Frogs (Pyxicephalidae: Nothophryne) for northern Mozambique inselbergs. Issue 1 (2nd January 2018) - Conradie, Werner; Bittencourt-Silva, Gabriela B.; Farooq, Harith M.; Loader, Simon P.; Menegon, Michele; Tolley, Krystal A.
ABSTRACT: Nothophryne Poynton, 1963 is a monotypic genus of frog, with the nominal species N. broadleyi found only on Mount Mulanje, in southern Malawi. Recent surveys in northern Mozambique, however, have uncovered at least four new species associated with four inselbergs (Mount Inago, Mount Namuli, Mount Ribáuè and Taratibu Hills). Previous phylogenetic analyses using mitochondrial genes suggest that each mountain isolate has an endemic species of Nothophryne . Herein we provide a rediagnosis of the genus and comparative diagnoses of four new species based on new material. ZooBank — urn:lsid:zoobank.org:pub:19C53BF3-BA52-4CAE-933F-5BBEE0AF0457